Efeito fisiológico de fungicidas no crescimento, produtividade e pós-colheita de batata (Solanum tuberosum L.) - Lopes, Édina Cristiane Pereira (2011)
The research was conducted in the experimental area of Department of Agronomy UNICENTRO in Guarapuava - PR. The objective was to evaluate the additive effects of fungicides fluazinam and metiram + pyraclostrobin in plant development, production and post harvest quality of potatoes (Solanum tuberosum L.). In addition to establishing a methodology for determination of leaf area based on the estimated regression equation for the length and width of leaves. We considered two stages, the first step performed in a completely randomized design with 5 treatments and 4 replicates, of which the T1 is the witness with fluazinam, T2, T3, T4, T5 are treated with different doses of pyraclostrobin + metiram furrow and in lumps. It was found that the parameters leaf number and leaf area index are benefited by the application of metiram (2.75 kg a.i. ha?¹) + pyraclostrobin (0.25 kg a.i. ha?¹) applied to lump or split in the groove and in piles, and this result is similar to the tuber yield, without affecting the classification of tubers, whereas the larger diameter. Regarding the methodology for assessing the leaf area it was found that the length of the leaf is an effective parameter to be used as an independent variable in estimating leaf area of potato cultivar Agate, functions by linear, quadratic, cubic, exponential growth, Gauss and Lorenz. The second stage was organized in a completely randomized design with split plots and four replications in a factorial 5x2x2. In the main plots were assessed five tillage treatments with fungicides (the same used in step 1), the subplots, the effects of applying or not metiram + pyraclostrobin at 68 days after planting, and in subsubplots evaluated the effects of washing or not the tubers. It was found that the application of pyraclostrobin + metiram 68 days after planting causes reduction in the greening of tubers and association management with application of pyraclostrobin + metiram 68 days after planting and tubers were not washed the management alternative that caused the lower rate of greening.